Infiltration characteristics of two instrumented residual soil slopes - Tsaparas, Illias (2011)
This paper presents the analysis of a 12 month long field study of the infiltration characteristics of two residual soil slopes in Singapore. The field measurements consist of rainfall data, runoff data of natural and simulated rainfall events, and pore-water pressure changes during infiltration at several depths and at several locations on the two slopes. The analysis of the field measurements identifies the total rainfall and the initial pore-water pressures within the two slopes as the controlling parameters for the changes in the pore-water pressures within the slopes during infiltration.